Modulation of Extracellular Matrix Composition and Chronic Inflammation with Pirfenidone Promotes Scar Reduction in Retinal Wound Repair - Laura Jahnke; Virginie Perrenoud; Souska Zandi; Yuebing Li; Federica Maria Conedera; Volker Enzmann (Cells, 2024)
Wound repair in the retina is a complex mechanism, and a deeper understanding of it is necessary for the development of effective treatments to slow down or even prevent degenerative processes leading to photoreceptor loss. In this study, we harnessed a laser-induced retinal degeneration model (532-nm laser photocoagulation with 300 μm spot size, 60 ms duration and 60 mV pulse), enabling a profound molecular elucidation and a comprehensive, prolonged observation of the wound healing sequence in a murine laser-induced degeneration model (C57BL/6J mice, 6–12 weeks) until day 49 post-laser. Our observations included the expression of specific extracellular matrix proteins and myofibroblast activity, along with an analysis of gene expression related to extracellular matrix and adhesion molecules through RNA measurements. Furthermore, the administration of pirfenidone (10 mg/kg via drinking water), an anti-inflammatory and anti-fibrotic compound, was used to modulate scar formation after laser treatment. Our data revealed upregulated collagen expression in late regenerative phases and sustained inflammation in the damaged tissue. Notably, treatment with pirfenidone was found to mitigate scar tissue formation, effectively downregulating collagen production and diminishing the presence of inflammatory markers. However, it did not lead to the regeneration of the photoreceptor layer.